Women’s shoes from the crypt of the church of the Name of the Holy Virgin Mary in Szczuczyn, Podlaskie Voivodship - Kulesz, Aleksandra (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
During the inventory-arranging works inside the western and eastern crypts under the presbytery conducted in the church of The Name of the Holy Virgin Mary in Szczuczyn, two examples of women’s eighteenth-century shoes were found. The first specimen represents a slip-on, leather shoe decorated with silk ribbons. The second one belongs to the class of footwear with a textile upper fastened with a buckle. Excellent conditions prevailing in the crypts ensured that the artefacts have been preserved in very good condition. This permitted detailed research on the raw materials used in constructing the footwear to be conducted. Textiles, leather and wood were subjected to microscopic analysis.
Keywords: crypts; footwear; 18th century; silk; leather; shoemaking; Poland